Examination of factors impacting spitting or vomiting among children under 5 years of age during seasonal malaria chemoprevention: a quantitative study in Burkina Faso, Chad, Nigeria and Togo - Chen Gao; Sikai Huang; Taiwo Ibinaiye; Benoît Sawadogo; Adama Traore; Cheick Saïd Compaoré; Fantche Awokou; Chukwudi A. Nnaji; Kevin Baker; Duoquan Wang; Sol Richardson (Tropical Medicine and Health)
Abstract Background Since 2012, the World Health Organization has recommended seasonal malaria chemoprevention (SMC) with sulfadoxine-pyrimethamine plus amodiaquine (SPAQ) for children aged 3–⁠59 months in regions where malaria transmission is seasonal. Full ingestion of SMC medicines without spitting or vomiting during a complete 3-day course is critical to ensure effectiveness of SMC medicines and to avoid development of antimalarial resistance. Although evidence suggests that spitting or vomiting is not rare, there is limited analytical evidence on potential factors associated with spitting or vomiting in SMC campaigns. Methods We utilized data from SMC coverage surveys conducted in Burkina Faso, Chad, Togo and Nigeria between 2020 and 2022. Episodes of spitting or vomiting were defined as SMC-eligible children spitting out most of the dose or vomiting the entire dose within 30 min of SPAQ administration as reported by primary caregivers. We conducted a cross-sectional study using mixed-effects logistic regression with variables including household socioeconomic variables and caregiver knowledge of SMC, to identify factors associated with spitting or vomiting. Results The proportion of SMC-eligible children spitting or vomiting SPAQ doses ranged from 1.81% in Nigeria to 4.36% in Chad. The odds of spitting or vomiting were lower among children administered medicines under community distributor (CD) supervision, and whose primary caregivers had a high degree of knowledge of SMC. Spitting or vomiting were negatively associated with caregiver adherence to AQ administration and caregiver reporting of children’s adverse reactions to SMC medicines. Over half of the children experiencing a spitting or vomiting episode did not receive a replacement dose from CDs. Redosing was positively associated with caregiver educational attainment, caregiver knowledge of SMC, and directly supervised medicine administration. Conclusions CD-supervised administration of SPAQ can strengthen community engagement strategies to enhance appropriate administration and full ingestion of SMC medicines according to the SMC delivery protocol.